Acute pancreatitis with eclampsia-preeclampsia syndrome and poor maternal outcome: two case reports and review of literature. (September 2015) - Gainder, Shalini; Arora, Parul; Saha, SC; Kaman, Lileswar
Acute pancreatitis in pregnancy is a rare entity and has been reported to be associated with preeclampsia in the literature. Fulminant pancreatitis may have a guarded prognosis despite intensive multidisciplinary management. Two cases of maternal mortality in women with acute pancreatitis noted in the setting of preeclampsia-eclampsia syndrome are reported here.